Data visualization with the programming language R. (1st October 2021) - Brennan, Paul
Abstract : Data visualization is an extremely valuable skill in science, finance and journalism. Learning to program will help reproducible data analysis and will increase the different types of visualization that can be generated. The statistical programming language R is a very useful programming language. The R community is friendly, supportive and very diverse including students, academics, health scientists, journalists and professional data scientists. An experience of R or another programming language such as Python or JavaScript will improve your science and your employment opportunities in and outside of research. Programming is a useful skill in education, finance, journalism and other areas too.